Synthesis and DPPH scavenging assay of reserpine analogues, computational studies and in silico docking studies in AChE and BChE responsible for Alzheimer's disease - Muhammad Yar; Muhammad Arshad; Ariba Farooq; Mazhar Amjad Gilani; Khurshid Ayub; Asma Ejaz; Anupriya Kumar; Ichiya Ninomiya (Universidade de São Paulo, 2015)
Alzheimer's disease (AD) is a fast growing neurodegenerative disorder of the central nervous system and anti-oxidants can be used to help suppress the oxidative stress caused by the free radicals that are responsible for AD. A series of selected synthetic indole derivatives were biologically evaluated to identify potent new antioxidants. Most of the evaluated compounds showed significant to modest antioxidant properties (IC50 value 399.07 140.0±50 µM). Density Functional Theory (DFT) studies were carried out on the compounds and their corresponding free radicals. Differences in the energy of the parent compounds and their corresponding free radicals provided a good justification for the trend found in their IC50 values. In silico, docking of compounds into the proteins acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), which are well known for contributing in AD disease, was also performed to predict anti-AD potential.